Kinerja Pemerintah Daerah dalam Menangani Retribusi Terminal : Studi Kasus Kabupaten Jayawijaya Propinsi Papua Pegunungan - Takdir, Soltan; Wetapo, Welius (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the terminal retribution management system at Jibama Terminal, Jayawijaya Regency, focusing on four indicators: collection, audit, utilization, and incentives. The method used is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the collection process is not carried out directly through the Transportation Agency office, audits are conducted sporadically, retribution funds have not been optimally utilized for terminal services, and officer incentives are not fully equitable. These findings reflect a gap between policy and implementation in the field. This study recommends the need for digitalization, strengthening human resource capacity, and inter-institutional collaboration to improve the effectiveness of the retribution management system. This study contributes to the development of a more adaptive and sustainable regional public service system..